Integration of wideband low noise amplifier with notch filter using defected microstrip structure - Saifullah, Nasrullah (2017)
Low noise amplifier is a crucial device in microwave wireless communication system which typically located in receiver parts. Wider bandwidth of low noise amplifier is theoretically much harder to be designed compared with narrowband. There are some designs has been presented in this thesis which covers wideband and ultra-wideband produced using Advanced Design System (ADS). Besides that, this research presents new methods designing low noise amplifier at wideband (4 GHz – 7 GHz) and ultra-wideband (3.1 GHz – 10.6 GHz) which cover 3 GHz and 7.5 GHz of bandwidth respectively. The first design operated at UWB frequencies implementing negative feedback which provide gain flatness throughout the frequency band. Furthermore, resistive matching provides good input and output matching for wide frequency range. The second design introduces inductive source degeneration which provides an improvement on S11 and S22 with very small degradation of noise figure. This design being supported by multi - section quarter wave transformer matching which provides wideband characteristic to the design. The third design is an improvement of second design by introducing balanced topology that provides good S11 and S22. The forth design implemented a wideband amplifier which designed using distributed amplifier with inductive source degeneration and multi-section quarter wave transformer matching. However, when designing wider bandwidth low noise amplifier, some existing standard such as IEEE 802.11 WLAN which operate at 5 GHz may cause an interference at the particular frequency band. As a way to prevent the interference from the current system that operates in the frequency band, a defected structure was presented to produce a notch response. Several designs of DMS was made which is G – Shaped, C - Shaped and U - Shaped to provide the best attenuation with desired rejection band. The best design which is U – Shaped DMS which has 15 dB attenuation and 1 GHz of rejection band. The integration of U – Shaped DMS ha been done for all of the design and the best design achieved is the second design which provide S11 and S22 of less than -8 dB from 3.1 GHz – 5 GHz and 6 GHz – 10.6 GHz. This design provide gain of more than 10 dB and noise figure of less than 4 dB. The achieved attenuation ratio is 26 dB with nearly 1 GHz rejection bandwidth. The benefit of integration of low noise amplifier with notch filter is the reduction of overall size while providing amplification and attenuation function simultaneously. This design is considered appropriate and a different solution for wireless and radar application without any additional or external connection between low noise amplifier and band – stop filter.